Pemodelan Otomasi Bak Sampah berbasis Sensitivitas Objek - M. D. Priangga; Simamora, S N M P (LOFIAN: Jurnal Teknologi Informasi dan Komunikasi, 2025)
Manual tasks that still rely heavily on human skill and discipline cannot yet match the superior results achievable through automation. The designed waste bin model ensures no physical contact between the end-user and the bin during disposal. This is achieved by installing a sensor to detect obstacles approaching the bin. When an obstacle, such as the end-user, is within a range of 80 to 40 centimeters from the sensor's line of sight, the bin lid will automatically open. Additionally, a sensor inside the bin detects the waste height from the lid. When the waste reaches a predefined height of 40 to 20 centimeters, a buzzer will sound, and a notification will be displayed indicating that the bin is full. The model was designed using the Wokwi simulator and implemented with an ESP-32 microcontroller. The model also employs an embedded-systems approach. The results demonstrate that the device successfully detects obstacles in front of the bin, ensuring non-contact between the end-user and the bin. The predefined waste height is also accurately detected by the sensor, triggering a notification on the Visual-Display Unit (VDU) and activating the buzzer.